Selective IgA Deficiency: Epidemiology, Pathogenesis, Clinical Phenotype, Diagnosis, Prognosis and Management. (January 2017) - Yazdani, R.; Azizi, G.; Abolhassani, H.; Aghamohammadi, A.
Abstract: Selective immunoglobulin A deficiency (SIgAD) is the most common primary antibody deficiency. Although more patients with SIgAD are asymptomatic, selected patients suffer from different clinical complications such as pulmonary infections, allergies, autoimmune diseases, gastrointestinal disorders and malignancy. Pathogenesis of SIgAD is still unknown; however, a defective terminal differentiation of B cells and defect in switching to IgA‐producing plasma cells are presumed to be responsible. Furthermore, some cytogenic defects and monogenic mutations are associated with SIgAD. There is no specific treatment for patients with symptomatic IgA deficiency, although prophylactic antibiotic therapy along with circumstantial immunoglobulin replacement with justification and supportive care (using a product that contains minimal IgA) could be helpful for patients with a severe phenotype. The epidemiology, pathogenesis, clinical phenotype, diagnosis, prognosis, management and treatment in patients with SIgAD have been reviewed.